Occupational exposures to noise resulting from the workplace use of personal media players - Autenrieth, Daniel Adam, author; Brazile, William Joseph, advisor; Sandfort, Delvin R., committee member; Lipsey, Tiffany, committee member (Colorado State University. Libraries, 2011)
This study examined the contribution of personal media player (PMP) use in the workplace to overall employee noise exposures at a Colorado manufacturing facility. A total of 24 workers, 12 high-background-noise exposed (HBNE) and 12 low-background-noise exposed (LBNE), were identified as having workplace PMP exposures. A questionnaire was administered to workers who use PMPs to assess occupational PMP use behaviors. In addition, the chosen listening level of each worker was measured using an ear simulator, and the background noise of each workstation was measured using a sound level meter. Chosen listening levels, background noise levels, and self-reported duration of use were used to estimate daily occupational noise exposures. The measured average background equivalent sound pressure levels were 81 and 59 dBA in high- and low-background noise exposure areas, respectively. The measured average free-field equivalent listening levels from PMPs were significantly greater for HBNE workers (85 dBA) as compared to LBNE workers (75 dBA) (p=0.0006). The average self-reported workplace PMP listening time was 3.6 hours per day. The estimated mean daily noise exposures were calculated from background noise and PMP use for both groups and were found to be below the American Conference of Governmental Industrial Hygienists (ACGIH) standard, specifically 84 dBA eight-hour time weighted average (TWA) for HBNE workers and 72 dBA for LBNE workers. However, 6 of 12 (50%) HBNE workers had estimated daily eight-hour TWA exposures greater than 85 dBA, while none of the LBNE workers exceeded ACGIH standards. The average difference between free-field equivalent listening levels and background noise levels (signal-to-noise ratio) was significantly higher in the LBNE workers (16 dBA) than HBNE workers (4 dBA) due to the selection of sound isolating headsets by HBNE workers. It is recommended that industries either limit workplace PMP use among HBNE workers or require output limiting technology to prevent occupational noise-induced hearing loss. Further research is needed to estimate the prevalence of occupational PMP use and to determine a background noise level threshold where allowing PMPs at work poses a significant hazard to worker health and safety.